The biological efficacy profile of BAX 855, a PEGylated recombinant factor VIII molecule. (2nd December 2014) - Valentino, L. A.; Cong, L.; Enockson, C.; Song, X.; Scheiflinger, F.; Muchitsch, E. M.; Turecek, P. L.; Hakobyan, N.
Summary Prophylaxis prevents joint and other bleeding episodes in patients with haemophilia A. Development of new factor concentrates with longer circulating half‐lives may encourage patients to start, continue or resume prophylaxis. The aim of this study was to compare the pharmacodynamic effect of a PEGylated full‐length recombinant factor VIII (rFVIII) concentrate with that of an unmodified rFVIII concentrate with respect to the duration of prophylactic efficacy in a murine model of haemophilic joint bleeding. Mice were pretreated with BAX 855 or unmodified rFVIII at specified times before right knee puncture to induce haemarthrosis; left knee joints served as controls. Joint bleeding was evaluated using a combination of visual and histological assessments. Administration of a single dose of unmodified rFVIII before joint puncture prevented haemarthrosis in mice up to 24 h, whereas pretreatment with BAX 855 protected the joint from bleeding up to 48 h. This pharmacodynamic study showed prolonged efficacy of BAX 855 compared to ADVATE in a haemophilia A mouse joint bleeding model. This finding supports the possibility of using BAX 855 to increase FVIII trough levels and/or extend the dosing interval in patients with haemophilia A on prophylaxis, which may potentially improve prophylactic efficacy and long‐term adherence.